Competitiveness of beef among NAFTA countries 1997-2008 - Omaña Silvestre José Miguel; Almora Bustos, Isael; Cruz Galindo Bartolomé; Hoyos Fernández Gabriela L.; Quintero Ramírez Juan Manuel; Fortis Hernández Manuel (Revista Mexicana de Ciencias Agrícolas, 2018)
This paper analyzes the trade competitiveness of beefamong member countries of the North American Free Trade Agreement (NAFTA): Mexico, Canada and the United States of America. The methodology used is by market indicators: market share, revealed comparative advantage coefficient (RCAC), penetration rate of imports (PRI) and production exposed to competition (PEC); for this, we used data from the period 1997-2008, comparing the average values of 1997-1999 against the average values of 2006- 2008. This allowed us to observe the development of the competitiveness of the 3 partners worldwide and also shows the evolution of the competitiveness of Canada and Mexico as a major supplier of beef in the U.S. market.